Evaluating the potential of innovations across aquaculture product value chains for poverty alleviation in Bangladesh and India - Bunting, Stuart W.; Bostock, John; Leschen, William; Little, David C. (Frontiers in Aquaculture, 2023)
Evidence is presented that innovation across aquaculture value chains can contribute to poverty reduction through income generation and increased consumption of nutritious aquatic foods. Innovation is defined and contextualized in relation to aquaculture development. Opportunities for aquaculture innovation across value chains for poverty reduction and sustainable production are described. Contemporary trends in aquaculture development in Bangladesh and India, with a focus on 2011-2020, are reviewed, as understanding transformative change to aquatic food systems during this period could benefit millions of poor and marginal consumers. Market-led commercial production, instigated by private sector entrepreneurs for domestic markets, has underpinned the surge in freshwater fish culture in key geographical locations. In contrast booms in shrimp production have been associated with export opportunities and related cycles of boom-and-bust have been described, with busts attributed to falling market prices and disease outbreaks. Innovation could safeguard supplies of affordable fish to poorer groups (especially young children and pregnant and breastfeeding women) and enable better health management of aquatic animals including coordination of surveillance and disease control measures. Innovation to effectively promote better management practices and integrated services provision to large numbers of small- and medium-scale producers could contribute to poverty reduction. Opportunities for future innovation to ensure that aquaculture development is sustainable are critically reviewed. Innovative strategies to add value to by-products and utilize waste resources could avoid negative environmental impacts, recycle nutrients and create income generating opportunities. A new paradigm for development assistance that identifies and supports promising innovation trajectories across jurisdictions, product value chains, institutional regimes and food systems is needed. Government agencies must be responsive to the needs of businesses throughout aquatic food systems and devise policies and regulatory regimes that support transformative and sustained growth of the aquaculture sector. Investment in capacity-building, education, research and training and action to promote an enabling institutional environment must be regarded as essential elements to maximize and share equitably the benefits arising and avoid potential negative impacts of inappropriate innovations.